2011
DOI: 10.1371/journal.pone.0018701
|View full text |Cite
|
Sign up to set email alerts
|

Agreeable Smellers and Sensitive Neurotics – Correlations among Personality Traits and Sensory Thresholds

Abstract: Correlations between personality traits and a wide range of sensory thresholds were examined. Participants (N = 124) completed a personality inventory (NEO-FFI) and underwent assessment of olfactory, trigeminal, tactile and gustatory detection thresholds, as well as examination of trigeminal and tactile pain thresholds. Significantly enhanced odor sensitivity in socially agreeable people, significantly enhanced trigeminal sensitivity in neurotic subjects, and a tendency for enhanced pain tolerance in highly co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 34 publications
2
42
1
1
Order By: Relevance
“…These data are consistent with reports that relate enhanced sensitivity in sensory systems that detect danger to increased neuroticism. 33 Our replication study confirmed this result, providing further evidence for an association between OR1A2 and Neuroticism (P ¼ 0.05). We also uncovered an association with glypican 6 (GPC6) (Supplementary Tables S1 and S2), which has also been linked with Eysenk Personality QuestionnaireNeuroticism.…”
Section: Neuroticismsupporting
confidence: 81%
See 1 more Smart Citation
“…These data are consistent with reports that relate enhanced sensitivity in sensory systems that detect danger to increased neuroticism. 33 Our replication study confirmed this result, providing further evidence for an association between OR1A2 and Neuroticism (P ¼ 0.05). We also uncovered an association with glypican 6 (GPC6) (Supplementary Tables S1 and S2), which has also been linked with Eysenk Personality QuestionnaireNeuroticism.…”
Section: Neuroticismsupporting
confidence: 81%
“…Little research has explored the influence of genetic variation in sensory sensitivity on personality traits, although studies have reported personality differences in visual, auditory, olfactory, tactile and gustatory capacities. 33,[46][47][48] Mettina et al 49 reported a significant positive relationship between olfactory sensitivity and neuroticism. Another study proposed that people scoring high in emotionality display had higher activation of the limbic system.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with more sensitive olfactory systems were found to be, on one hand, more sociable, empathic, out-going, agreeable and, on the other hand, more emotional, self-conscious, and anxious. Such a personality pattern might develop, in line with the model of Croy et al (2011), as an effect of the reception of rich olfactory input, possibly containing information relevant to social cognition. As such, individuals with sensitive olfaction receive more sociochemosensory stimuli, which allows them to unconsciously infer accurate information about people they interact with.…”
Section: Introductionmentioning
confidence: 69%
“…While no relationship was observed between olfactory sensitivity and agency, those with higher scores on communion had significantly better score in olfactory sensitivity task. This effect can be explained with sensory filter theory (Croy et al 2011), according to which the number of social odors processed by an individual is determined by the capacity of the olfactory system. A large amount of socially relevant information contained in the received odors makes an individual more aware of their social environment, in turn, enhancing the development of communal personality traits.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation